ANALISIS TINGKAT BAHAYA BEKERJA DI KETINGGIAN DI AREA UNLOADER PT DERMAGA PERKASAPRATAMA BALIKPAPAN - Zainal, Isradi Zainal; Monica, Dea Monica; Noeryanto, Noeryanto (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
The purpose of this study is to analyze and find out the level of danger faced by workers in working activities at heights and efforts to control occupational safety and health at PT Dermaga Perkasapratama. This research is qualitative. This research is qualitative. Primary data were collected by field observations and interviews and secondary data obtained from the company. Resource persons in this study were 5 (five) workers and 1 mechanical unloader Data obtained were analyzed descriptively using HIRAC (Hazard Identification and Risk Assessment Control) tables and compared with existing standards and theories. The method used by the author in identifying hazards and risk assessments refers to the IBPR rules of PT. Perkasapratama Pier. The results showed that there were 2 (two) hazard activities identified. The results of the risk assessment were 21 (twenty-one). And 12 (twelve) hazards with moderate risk and 10 hazards with low risk. Types of hazard control that have been carried out include technical, administrative and the supply of personal protective equipment. Company management is advised to review the company's IBPR documents by directly reviewing the location, work tools, and ways of working so that the potential hazards that may be present in an activity can be identified and its control measures determined.